2020
DOI: 10.1371/journal.pcbi.1008012
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the performance of methods for copy number aberration detection from single-cell DNA sequencing data

Abstract: Single-cell DNA sequencing technologies are enabling the study of mutations and their evolutionary trajectories in cancer. Somatic copy number aberrations (CNAs) have been implicated in the development and progression of various types of cancer. A wide array of methods for CNA detection has been either developed specifically for or adapted to singlecell DNA sequencing data. Understanding the strengths and limitations that are unique to each of these methods is very important for obtaining accurate copy number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 57 publications
1
60
0
Order By: Relevance
“…Since HMM-based methods produce both a segmentation and absolute copy numbers at the same time, the selection of ploidy is essential in determining the copy number profile genome-wide. We observed that HMMcopy does not always select the right ploidy [54], leading to wrong copy number inference for the entire genome. Visualization of the CNA profiles of a group of cells is usually done by heatmaps, one example of which can be seen in [27].…”
Section: Calling the Absolute Copy Numbersmentioning
confidence: 83%
See 4 more Smart Citations
“…Since HMM-based methods produce both a segmentation and absolute copy numbers at the same time, the selection of ploidy is essential in determining the copy number profile genome-wide. We observed that HMMcopy does not always select the right ploidy [54], leading to wrong copy number inference for the entire genome. Visualization of the CNA profiles of a group of cells is usually done by heatmaps, one example of which can be seen in [27].…”
Section: Calling the Absolute Copy Numbersmentioning
confidence: 83%
“…One advantage of HMMcopy and AneuFinder is their ability to simultaneously infer segmentation and absolute copy numbers. As shown in [54], despite the possibility of selecting the wrong ploidy, HMMcopy achieved high precision and recall (around 0.8 for recall and 0.7 for precision) in both segmentation and copy number inference in a simulation study of single cells. Another advantage of HMMcopy is that its computational burden is relatively light.…”
Section: Hmmcopy and Aneufindermentioning
confidence: 96%
See 3 more Smart Citations